Nanomedicine in diagnostics and therapy of cardiovascular diseases: Beyond atherosclerotic plaque imaging - Cicha, Iwona; Lyer, Stefan; Alexiou, Christoph; Garlichs, Christoph (Nanotechnology Reviews, 2013)
Atherosclerosis results from the accumulation of the modified lipoproteins within the artery walls, which triggers complex vascular inflammatory processes. Although the pharmacologic agents for the treatment of clinical manifestations of atherosclerosis are available, their systemic delivery has serious disadvantages, such as considerable side effects or low efficacy at tolerated doses. Moreover, the treatment of atherosclerosis using the interventional techniques bears further shortcomings: the implanted stents require a lengthy antiplatelet therapy and carry the risk of in-stent restenosis. In the surgical approach to atherosclerosis, apart from the overall risk of open heart surgery, the lack of adequate venous material for bypasses constitutes a common problem. The nanotechnology has the potential to overcome the disadvantages of the current therapy of atherosclerosis, e.g., by the formation of nanosized assemblies for the earlier detection of atherosclerotic lesions and for cell-specific delivery of therapeutics. Replacing the current systemic pharmacological approach by a locally targeted treatment of plaques can substantially minimize the adverse effects, by lowering the drug cytotoxicity and reducing the required dosage. Moreover, a new generation of nanotechnological approaches to the revascularization procedures is now emerging, e.g., vascular tissue engineering utilizing the magnetic nanoparticles or the design of stents with the reduced risk of thrombosis and restenosis. This review discusses the possible applications of the nanomedical approaches in the treatment of cardiovascular diseases.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Atherosclerosis; Nanoparticles; Plaque imaging; Stent design; Vascular tissue engineering